SCREENING, PROGNOSTIC EVALUATION AND SURGERY IN LUNG CANCER: REVIEW ARTICLE - de Oliveira e Silva, Jaine; Rayone de Freitas, Marcos (Health and Society, 2023)
Lung cancer is currently the neoplasm with the highest mortality among men and the second leading cause of mortality in women. OBJECTIVE : to review the importance of early screening and therapeutic possibilities in lung cancer DISCUSSION: The main risk factor for the development is smoking, however, other factors are also related, such as: presence of preexisting lung disease, occupational exposure (asbestos, uranium, chromium, alkylating agents), family history of lung cancer and previous lung cancer. In clinical practice, the prognosis is related to the staging of the disease and the histological type. In most cases, the diagnosis is late with the disease in an advanced stage, making curative treatment impossible. CONCLUSION: Due to the high mortality and the impact on treatment, it is necessary to recommend earlier screening of the population with risk factors, since treatment in the initial phase improves people’s survival and impacts on mortality indicators. METHODOLOGY: This is a literature review study. The research was guided by bibliographic articles from the Scielo, Lilacs; in addition to recommendations available on sites such as the National Cancer Institute and the American Cancer Society.